Chemical versus physical pressure effects on the structure transition of bilayer nickelates - Gang Wang; Ningning Wang; Tenglong Lu; Stuart Calder; Jiaqiang Yan; Lifen Shi; Jun Hou; Liang Ma; Lili Zhang; Jianping Sun; Bosen Wang; Sheng Meng; et al. (npj Quantum Materials)
Abstract The observation of high-T c superconductivity (HTSC) in concomitant with pressure-induced orthorhombic-tetragonal structural transition in bilayer La3Ni2O7 has sparked hopes of achieving HTSC by stabilizing the tetragonal phase at ambient pressure. Chemical pressure, introduced by replacing La3+ with smaller rare-earth R 3+ has been considered as a potential route. However, our experimental and theoretical investigation reveals that such substitutions, despite causing lattice contraction, actually produce stronger orthorhombic distortions, requiring higher pressures for the structural transition. A linear extrapolation of P c versus the average size of A-site cations (<r A >), yields a putative critical value of <r A >c ≈ 1.23 Å for P c ≈ 1 bar. The negative correlation between P c and <r A > indicates that replacing La3+ with smaller R 3+ ions is unlikely to reduce P c to ambient pressure. Instead, substituting La3+ with larger cations like Sr2+ or Ba2+ might be a feasible approach. Our results provide guidance for realizing ambient-pressure HTSC in bilayer nickelates.